EFL Teachers Perception toward the Use of Beyond International Textbook - Muzakky, Muhammad; Albiansyah, Albiansyah (Universitas Negeri Semarang, 2021)
This study aims to explore the teachers perception on using the beyond textbook that is from an international publisher. The study used descriptive qualitative design. The open-ended questionnaire was used to explore the teachers perception. The participants of the study were three English teachers, two of them are from SMPIT Al Muqorrobin-Depok and one is from SMPI Al Ikhlas-South Jakarta. The finding revealed that the teacher has a positive perception of the textbook. It has accordance with the requirements of the good book. The content is aligned with the Indonesia curriculum. It also involved four basic language skills as well as its language knowledge. However, the textbook has very minimal local cultural understanding and doesnt facilitate all learners cognitive level. For further research, it is suggested to have the study in Bilingual or senior school in order to find the maximum result toward the implementation of the textbook.